PENGARUH BRIEFING KERJA DAN PERAN SUPERVISOR TERHADAP KINERJA KARYAWAN PADA PT.GMF AEROASIA Tbk. - Dadang, Dadang; Heriyanto, Feri (Universitas Muhammadiyah Tangerang, 2020)
The purpose of this study was to determine the effect of work briefing and supervisor role on the employee performance of PT. GMF Aeroasia Tbk. in Third Party Line Maintenance Unit at Soekarno Hatta International Airport. This study uses a quantitative approach. The population in this study were 150 employee of PT. GMF Aeroasia Tbk. in Third Party line Maintenance unit at Soekarno Hatta International Airport. The sampling technique used was purposive sampling and obtained a sample of 60 respondents. The data analysis technique used is multiple linear regression. The results showed that partially the work briefing had a positive and significant effect on employee performance. For supervisor role variables partially have a positive and significant effect on employee performance. Simultaneously work briefing and supervisor role have a positive and significant effect on purchasing decisions. The ability of work briefing variables and supervisor role in explaining purchasing decisions is 89.1% as indicated by the R square value of 0.891 while the remaining 10.9% is influenced by other factors not included in the research model.